Украино-ананские параллели в погребальной обрядности / Ukrainian-Alan parallels in the funeral rites - K.Ju Rahno (Материалы по археологии и истории античного и средневекового Крыма, 2011)
The article is dedicated to the analogous rites in the funeral ceremonials of the medieval Alans, described by Giosafat Barbaro, and the Ukrainians, described by Jean Benoît Scherer. These rites can be regarded as one of the results of the cultural interaction between the Iranophone population of the Eastern European steppes and the Slavs.